PERHITUNGAN STRUKTUR BETON GEDUNG SEKOLAH DASAR MUHAMMADIYAH METRO PUSAT (KAMPUS 2) - - Masherni (TAPAK [Teknologi Aplikasi Konstruksi] : Jurnal Program Studi Teknik Sipil, 2014)
The result of structural building calculation based on the method and rules above, it gain the product design of structural concrete planning that very detail. The carefulness calculating, accuracy in a load assumption as a crussial factor which has notice on structural building planning.